PENENTUAN KENDARAAN MOBIL BEKAS MENGGUNAKAN METODE TOPSIS - Faizal Muharram (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
Information about used cars being sold can help consumers in buying a vehicle. But sometimes humans often forget, especially if the criteria are very much like the price of cars, interior accessories, exterior accessories, passenger capacity and production years so that consumers often experience errors in the selection of used vehicles to be bought. Therefore we need a system that can provide recommendations using appropriate methods, the following is a decision support system method including Fuzzy Multiple Attribute Decision Making. One mechanism for solving FMADM problems by applying the TOPSIS (Technique For Others Reference by Similarity to Ideal Solution) method TOPSIS uses the principle that the chosen alternative must have the shortest distance from the positive ideal solution and the farthest from the negative ideal solution from a geometric point of view using Euclidean distance to determine the relative proximity of an alternative to the optimal solution. The positive ideal solution is defined as the sum of all the best values that can be achieved for each attribute, while the negative ideal solution consists of all the worst values achieved for each attribute. Keywords: Topsis, Ideal solution, Ideal Positive, Ideal Negative